(untitled) - Goleman, Daniel (San Francisco, 2012)
A new integration of Goleman's emotional, social, and ecological intelligenceThis book portrays inspiring educators, activists, and students who embody a new integration of emotional, social, and ecological intelligence--or what the authors refer to as engaged ecoliteracy. It builds on the success of bestselling author Daniel Goleman's emotional and social learning, and shows how educators are extending the cultivation of these essential dimensions of human intelligence to include knowledge of and empathy for all living systems. With stories that range from the Arctic to Appalachia and New York to New Orleans it illustrates dynamic education and engagement about some of the most important ecological issues of the day, from oil and coal to food and water. It also features a comprehensive professional development guide and the five processes of engaged ecoliteracy.
Keywords: Sinh thái học người,Human ecology; Dạy và học,Study and teaching